A compact quad-element serrated boundary fractal planar antenna for multi-band mmWave 5G/6G wireless applications - Tathababu Addepalli; Thota Vidyavathi; Maragani SatishKumar; Gudapati Divya; Morasa Balaji; Sivasubramanyam Medasani; Mohammad Sami Zidan; Imran Mohd Ibrahim; Ahmed Jamal Abdullah Al-Gburi (PLoS ONE, 2026)
This paper proposes a compact serrated boundary fractal planar quad-element MIMO antenna engineered for multi-band millimeter-wave (mmWave) 5G/6G systems. The structure is designed and developed on 30 × 30 mm 2 size rogers’ material of thickness 0.8 mm. The proposed design evolves progressively through three stages, from a conventional rectangular patch to a compact, fractal-inspired geometry featuring embedded slots and symmetrical serrated arrow-shaped protrusions. This structural evolution significantly enhances electromagnetic coupling, current path diversity, and multi-band resonance behaviour. The antenna resonates at four distinct mmWave frequency bands 24.5 GHz, 33.5 GHz, 38.0 GHz, and 44.0 GHz, covering key portions of the 5G spectrum. The compact quad-element layout exhibits high isolation, notable peak gain, and favourable diversity metrics, including ECC (Sim ≤ 0.00008, Mea ≤ 0.00010), DG (Sim ≤ 10 dB, Mea ≤ 10 dB), TARC (Sim ≤ −10 dB, Mea ≤ −9 dB), CCL (Sim ≤ 0.005 bits/s/Hz, Mea ≤ 0.010 bits/s/Hz), and MEG (Sim ≤ −3 dB, Mea ≤ −3 dB), all within ITU-recommended limits, collectively contributing to robust MIMO performance. Its compact size, structural symmetry, and multiband performance make it an excellent candidate for low-latency, and interference-resilient wireless applications in next-generation vehicular and IoT communication systems.